On coincidence and common fixed points of nearly densifying mappings - Zeqing Liu; Jeong Sheok Ume (International Journal of Mathematics and Mathematical Sciences)
Coincidence and common fixed point theorems for certain new classes of nearly densifying mappings are established. Our results extend, improve, and unify a lot of previously known theorems.